Oxidation-resistant seawater desalination reverse osmosis membrane as well as preparation method and application thereof
By conducting interfacial polymerization on the porous support layer of the reverse osmosis membrane, an ultra-thin polyamide separation layer is formed, which solves the problem of easy oxidation of the existing membrane when the oxidant is contacted, and achieves the improvement of high throughput, high desalination rate and oxidation resistance.
Patent Information
- Application Number
- CN202510220855.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-04-22
AI Technical Summary
Existing reverse osmosis membranes are easily oxidized when exposed to oxidant, resulting in a decrease in desalination rate and when the coating is added to improve oxidation resistance, the flux will decrease, resulting in additional negative effects.
Fourier transform attenuated total reflection infrared spectrometer (ATR-FTIR) and X-ray photoelectron spectrometer (XPS) were used to conduct interfacial polymerization reaction by contacting the aqueous multifunctional amine solution and the oil-phase solution of polyfunctional acid chloride and polyfunctional thiol on the porous support layer to form an ultra-thin polyamide separation layer to improve the oxidation resistance of the film.
The high throughput and high desalination rate of the polyamide composite film are achieved, while greatly improving the oxidation resistance of the film is avoided, and the preparation method is relatively simple.
Smart Images

Figure BDA0005288680190000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane technology and relates to an oxidation-resistant seawater desalination reverse osmosis membrane, a preparation method and application thereof. Background Art
[0002] Reverse osmosis membrane technology is currently the most commonly used seawater desalination technology. Fresh water filtered by seawater desalination reverse osmosis membrane elements is widely used in municipal water supply and industrial water.
[0003] Cadotte et al. published a method for preparing a reverse osmosis membrane in US Pat. No. 4,277,344, using porous polysulfone as a support layer and obtaining an ultra-thin polyamide layer through interfacial polymerization. The functional layer only allows water molecules to pass through, while salt ions and other substances are retained.
[0004] In the water treatment process, sodium hypochlorite is the most common oxidizing bactericide and is widely used in the pretreatment process. Although sodium bisulfite is added for reduction before the reverse osmosis membrane process, residual chlorine occasionally enters the downstream reverse osmosis membrane process, causing the reverse osmosis membrane to be oxidized and the desalination rate to decrease. Therefore, improving the oxidation resistance of the reverse osmosis membrane will help to increase the product life. There have been a lot of studies on improving the oxidation resistance of reverse osmosis membranes.
[0005] The technical solutions for adding coatings to improve oxidation resistance are: CN115337800B, on the first polyamide layer, a second polyamide layer is formed by a dihydrazide compound, which not only improves the membrane desalination rate, but also improves oxidation resistance; CN115672033A, on the first polyamide layer, a cross-linked coating of 2-(2,3-epoxypropylthio)thiophene, polyethylene glycol diglycidyl ether and 3,4-diamino-n-(3-trifluoromethyl-phenyl)-benzenesulfonamide is applied to improve oxidation resistance. However, the membrane flux obtained by the above scheme will decrease due to the added coating, resulting in additional negative effects.
[0006] The scheme of changing the chemical structure of the polyamide layer includes: CN115945072A, which uses an oxidant to treat the first polyamide layer, uses a phenolic mixture to treat it again, and then forms a protective layer on its surface through cross-linking of a polymer material to achieve anti-oxidation performance. This scheme has complicated steps and is difficult to implement. Summary of the invention
[0007] The purpose of the present invention is to provide an improved polyamide composite membrane, a preparation method and its application in view of the deficiencies in the prior art. The polyamide composite membrane of the present invention has excellent flux and desalination rate, as well as oxidation resistance, and can be used for seawater desalination.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] In a first aspect, the present invention provides a polyamide composite membrane, wherein a polyamide separation layer is provided on a porous support layer of the polyamide composite membrane, and the separation layer has the following characteristics:
[0010] 1. Using Fourier transform attenuated total reflection infrared spectrometer (ATR-FTIR), 2561cm -1 The peak height is 1661cm -1 The peak height ratio is 0.03-0.15%,
[0011] 2. The surface sulfur atom content measured by X-ray photoelectron spectroscopy (XPS) analysis is 0.5-2.5 mol%.
[0012] In some specific embodiments, the polyamide composite membrane of the present invention includes: 1. a non-woven fiber layer (preferably a polyester non-woven fiber layer) with a thickness of about 80-110 microns, which is obtained by wet papermaking of long and short fibers with a diameter of 10-20 microns and hot pressing. It has a smooth surface, a loose and porous interior, and a certain air permeability, which provides mechanical strength for the entire membrane; 2. a porous support layer with a thickness of about 30-60 microns, which obtains an asymmetric pore structure through wet phase transformation, and a surface pore diameter of about 10-50 nanometers, providing a smooth support layer for the polyamide separation layer; 3. an ultra-thin polyamide separation layer with a thickness of about 30-500nm, which plays the final desalination role, is obtained through interfacial polymerization, and has a pore diameter of about 0.1-2nm.
[0013] Polyester nonwoven fabric preferably has an air permeability of 0.5-2.5cm 3 / cm 2 / s, test method refer to JIS L 109-A.
[0014] In a second aspect, the present invention also provides a method for manufacturing the polyamide composite film, comprising the following steps:
[0015] (1) a polyfunctional amine aqueous solution containing a polyfunctional epoxy compound and / or a polyfunctional double bond compound and an oil phase solution containing a polyfunctional acyl chloride and a polyfunctional thiol are contacted and reacted on a porous support layer to form a polyamide separation layer;
[0016] (2) After the interfacial polymerization reaction is completed, heating and / or ultraviolet irradiation is performed to allow the reaction to proceed fully to obtain a polyamide composite membrane.
[0017] The polymer is dissolved in a polar solvent to obtain a uniform polymer solution, which is then degassed and filtered and coated on a non-woven fabric. The coated non-woven fabric is immersed in pure water to complete solidification and then rinsed to obtain a porous support layer.
[0018] The porous support layer, wherein the polymer is selected from polysulfone, polyethersulfone, polyphenylsulfone, polyphenylene sulfide, polyphenylene ether, polyphenylene sulfide sulfone, polyamide, polyimide, polyester, vinyl polymer, cellulose polymer, wherein the vinyl polymer is selected from polyethylene, polypropylene, polyvinyl chloride, polyacrylonitrile, etc., and the cellulose polymer is selected from cellulose acetate, cellulose nitrate, etc., and can be a blend of one or more thereof. In terms of chemical, mechanical and thermal stability, the polymer is preferably polysulfone;
[0019] The polar solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, preferably N,N-dimethylformamide. Optionally, the polar solvent also includes a porogen selected from ethylene glycol methyl ether, water, and polyethylene glycol.
[0020] The water tank in which the coated nonwoven fabric is immersed is called a coagulation bath water tank, in which the polymer solution is cured at a temperature of 5-30°C, preferably 10-25°C.
[0021] In the preparation method, step (1) specifically includes (1-1) and (1-2), wherein:
[0022] (1-1) The aqueous solution is coated on the surface of the porous support layer. The coating method can be dip coating, slit coating, spraying, pouring, etc. After coating, the excess aqueous solution is removed by using an extrusion roller, air knife, scraper, oven, etc.
[0023] The aqueous phase solution contains a polyfunctional amine with a functionality of 2-4, which can be one or a mixture of several, and can be aromatic, such as m-phenylenediamine, p-phenylenediamine, 1,3,5-triaminobenzene, or aliphatic, such as ethylenediamine, piperazine, diethylenetriamine, triethylenetetramine, preferably m-phenylenediamine. The concentration range of the polyfunctional amine in the aqueous phase solution is 1-8wt%, preferably 1.5-3.5wt%.
[0024] The aqueous phase solution also contains a multifunctional epoxy compound and / or a multifunctional double bond compound, which can be one or a mixture of several, and can be any one or a combination of at least two of polyethylene glycol diglycidyl ether (PEGDE), 15 ethoxylated trimethylolpropane triacrylate (TMP15EOTA), bisacrylamide (MBA), etc., with a concentration range of 0.1-3wt%, preferably 1-2.5wt%.
[0025] (1-2) After removing the excess water phase, a non-polar oil phase solution containing multifunctional acyl chloride and multifunctional thiol is coated on the surface of the porous support layer to carry out an interfacial polymerization reaction. The coating method can be dip coating, slit coating, spray coating, or shower coating.
[0026] The multifunctional acyl chloride is selected from difunctional acyl chloride and / or trifunctional acyl chloride, the difunctional acyl chloride is selected from any one of terephthaloyl chloride, isophthaloyl chloride, naphthalene dicarboxylic acid chloride, etc. or a combination of at least two thereof, and the trifunctional acyl chloride is selected from any one of trimesoyl chloride, 1,3,5-cyclohexanetricarboxylic acid chloride, 1,2,4-cyclobutanetricarboxylic acid chloride, etc. or a combination of at least two thereof; the difunctional acyl chloride or the trifunctional acyl chloride can be used alone or in combination of two or more thereof. In view of availability and operability, the multifunctional acyl chloride is preferably trimesoyl chloride;
[0027] The multifunctional thiol is selected from a difunctional thiol or a trifunctional thiol or more, and the difunctional thiol is selected from 1,2-ethanedithiol, 1,3-propanedithiol, 1,2-propanedithiol, 2,3-butanedithiol, 1,2-butanedithiol, 1,4-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,8-octanedithiol, 1,9-nonanedithiol, 1,10-decanedithiol, 1,2-benzenedithiol, 1,3-benzenedithiol, 1,4-benzenedithiol, tetra(ethylene glycol)dithiol, hexa(ethylene glycol) Dithiol, and poly (ethylene glycol) dithiol with a number average molecular weight of 1000-8000, etc., the three or more functional thiols are selected from trimethylolpropane tris (thioglycolate) ester (TMTG), trimethylolpropane tris (3-mercaptopropionic acid) ester (TMPMP), tetrakis (3-mercaptopropionic acid) pentaerythritol ester, etc., the multifunctional thiol can be used alone or in combination of two or more, and the multifunctional thiol is preferably trimethylolpropane tris (thioglycolate) ester (TMTG) in terms of availability and operability;
[0028] The multifunctional acyl chloride and the multifunctional thiol are dissolved in a non-polar solvent to prepare an oil phase solution for use, wherein the non-polar solvent is selected from any one or a combination of at least two of linear alkanes, isomeric alkanes, and aromatic solvents; the linear alkanes are selected from any one or a combination of at least two of hexane, octane, nonane, decane, etc., the isomeric alkanes are selected from any one or a combination of at least two of Isopar E, Isopar G, Isopar L, etc., the aromatic solvents are selected from any one or a combination of at least two of toluene, xylene, trimethylbenzene, etc., and Isopar G is preferred in terms of cost and safety;
[0029] Preferably, the concentration of the multifunctional acid chloride in the oil phase solution is 0.08-0.6 wt%, preferably 0.1-0.4 wt%;
[0030] The mass concentration ratio of the multifunctional amine monomer in the aqueous solution to the acyl chloride in the oil phase solution is preferably 4-40:1;
[0031] Preferably, the concentration of the multifunctional thiol in the oil phase solution is 0.01-0.1 wt %.
[0032] Preferably, in order to regulate the reaction rate and the performance of the final product, the interfacial polymerization reaction can change the temperature of the polar solvent phase and the non-polar solvent phase involved in the reaction, control the interfacial polymerization reaction time, and can also add acid binding agents (such as sodium hydroxide, camphorsulfonic acid and triethylamine salts), solubilizers (such as toluene), complexing agents (such as phosphate compounds), humectants (such as glycerol), photoinitiators (such as benzophenone), etc. to the formula; as a preferred embodiment, the aqueous phase solution of the present invention adopts a scheme that, based on the total mass of the aqueous phase solution as 100%, its composition includes 1-8wt% of multifunctional amine monomers, 1-6wt% of camphorsulfonic acid, 0.5-3wt% of triethylamine, 0.1-2wt% of multifunctional epoxy and / or multifunctional double bond compounds, and water;
[0033] The interfacial polymerization reaction has a reaction temperature of room temperature, preferably 20-30° C., and a reaction time of 0.5-5 min, preferably 1-2 min.
[0034] In the preparation method, the heating treatment in step (2) is preferably carried out in an oven, the oven temperature is preferably 40-90°C, and the drying time is 0.5-2 minutes. The ultraviolet irradiation treatment is preferably carried out with a 254nm short-wavelength ultraviolet lamp, the irradiation power is preferably 60-160w / cm, and the irradiation time is 1-20 seconds.
[0035] The polyamide composite membrane prepared by the above method of the present invention comprises a polyamide layer obtained in the first step, which contains the reaction product of epoxy and / or double bond compounds and thiol. After further heating and / or ultraviolet irradiation in the second step, the reaction is fully carried out to obtain an interpenetrating cross-linked polymer network, and finally a polyamide composite membrane with excellent performance and simple production control is obtained.
[0036] By using attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), the 2561 cm -1 The peak height is 1661cm -1 The ratio of the peak heights at the sites can be used to determine the proportion of thiol introduced into the entire polyamide membrane. The proportion of thiol exposed on the surface of the polyamide membrane can be determined by analyzing the surface sulfur atom content measured by X-ray photoelectron spectroscopy (XPS).
[0037] The beneficial effects of the present invention are:
[0038] The ratio of thiols inside the polyamide membrane can control the size of the pore structure inside the polyamide affected by the thiol polymer, which provides a guarantee for the stability of the desalination rate and flux. By characterizing the sulfur atom content on the membrane surface, on the one hand, it ensures that the surface properties of the membrane do not change dramatically, and on the other hand, the introduced thiol provides excellent antioxidant properties, providing a significant improvement in antioxidant properties.
[0039] Compared with the prior art, the preparation method of the present invention is simple, and the prepared polyamide composite membrane can not only maintain the water production and desalination rate of the existing polyamide membrane, but also has the advantage of greatly improved antioxidant performance, and has good prospects for industrialization. DETAILED DESCRIPTION
[0040] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0041] Main raw material sources
[0042] Polysulfone, purchased from BASF, Germany, Ultrason S6010.
[0043] Nonwoven fabric, purchased from Zhejiang Qinglan Membrane Technology Co., Ltd., R80.
[0044] Polysulfone-based membrane, preparation method: dissolve polysulfone in N,N-dimethylformamide to prepare a solution with a solid content of 18%, use a 250-micron thick wet film preparation device to coat the polysulfone solution on the surface of the non-woven fabric, stay in the air for 4-5 seconds, soak the non-woven fabric in pure water at room temperature, and complete the phase inversion after soaking for 5 minutes. Soak the polysulfone-based membrane that has completed the phase inversion in pure water at room temperature, change the water every 2 hours, and after fully cleaning the residual solvent, cut it for use.
[0045] Unless otherwise specified, the other reagents were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. and were reagent grade raw materials.
[0046] Main test methods
[0047] Desalination rate and flux test method: refer to the desalination rate and flux test method in GB / T32373-2015 "Reverse Osmosis Membrane Test Method", the test liquid temperature is 25℃, the pH value is 7.0, the test liquid is 32000ppm sodium chloride aqueous solution, and the test pressure is 5.5MPa.
[0048] Oxidation resistance test method: After the membrane with tested desalination rate and flux is immersed in a 25℃ sodium hypochlorite aqueous solution with a pH value adjusted to 7.0 and an effective chlorine concentration of 100ppm for 24 hours, the membrane is rinsed with pure water, and the desalination rate and flux are tested again. The degree of decrease in desalination rate before and after immersion is compared to judge the quality of the membrane's oxidation resistance.
[0049] Fourier transform attenuated total reflection infrared spectroscopy test method (ATR-FTIR):
[0050] The membrane was cleaned by immersion in pure water and then dried. A Fourier transform infrared spectrometer (Perkin Elmer Spectrum One FT-IR) and a universal total reflectance (ATR) sampling accessory were used to analyze the membrane at 4 cm -1 The ATR sampling accessory is preferably equipped with a single reflection diamond / ZnSe crystal. -1 The single point baseline at 2561cm -1 The mercaptan peak height is measured at 1765 cm -1 The single point baseline at 1661cm -1 The amide peak height is measured at 2561 cm -1 The peak height is 1661cm -1 Peak height ratio.
[0051] X-ray Photoelectron Spectroscopy Test Method (XPS):
[0052] The membrane was cleaned by soaking in pure water and then dried. The element content on the surface of the dried membrane was tested using an X-ray photoelectron spectrometer (ThermoFischer, ESCALAB 250Xi, USA). The vacuum degree of the analysis chamber was 4x10 -9 mbar, the excitation source is Al ka ray (hv = 1486.6eV), the working voltage is 14.6kV, the filament current is 13.5mA, and the signal accumulation is performed for 20 cycles. The test passing energy is 20ev, the step length is 0.1eV, and the charge correction is performed with C1s = 284.8eV binding energy as the energy standard, and the contents of C, N, O, and S are detected respectively. The S atomic ratio is the molar ratio of the S element to all the above-mentioned detected elements.
[0053] Comparative Example 1
[0054] The method comprises the following steps: at room temperature of 20°C, a cut polysulfone base membrane is attached to a plate frame, the size of the plate frame is a square with a side length of 10 cm and a thickness of about 8 mm, 20 ml of an aqueous solution containing 2 wt% of m-phenylenediamine, 6 wt% of camphorsulfonic acid and 3 wt% of triethylamine is poured on the surface of the polysulfone base membrane surrounded by the plate frame, 5 minutes are waited, the aqueous solution in the plate frame is poured out, and excess aqueous phase on the surface of the base membrane is squeezed out with a rubber roller, and then 20 ml of an n-hexane solution containing 0.1 wt% of trimesoyl chloride and 10 wt% of mesitylene is poured on the surface of the polysulfone base membrane to carry out an interfacial polymerization reaction, 1 minute is waited, and then excess oil phase is poured out to obtain a polyamide composite membrane, the polyamide composite membrane is placed in a 40°C blast oven, reacted for 2 minutes, the reaction is completed, and rinsed in pure water to obtain a polyamide composite membrane.
[0055] The membrane was subjected to various performance tests, and the results are shown in Table 2.
[0056] Comparative Example 2
[0057] The polyamide composite membrane that has completed interfacial polymerization in Comparative Example 1 but has not yet entered the oven for heating was irradiated under a UV lamp with a wavelength of 254 nm and a power of 160 w / cm for 1 second to complete the reaction, and then rinsed in pure water to obtain a polyamide composite membrane.
[0058] The membrane was subjected to various performance tests, and the results are shown in Table 2.
[0059] Examples 1-3, Comparative Examples 3-4
[0060] On the basis of Comparative Example 1, water phase additives and / or oil phase additives are added to obtain Examples 1-3, as well as Comparative Examples 3 and 4.
[0061] Example 4
[0062] On the basis of Comparative Example 1, water phase additives and oil phase additives were added, and the oven temperature was adjusted to 90° C. and the reaction time was 0.5 minutes.
[0063] Example 5
[0064] On the basis of comparative example 2, water phase additives and oil phase additives were added, and the power of the ultraviolet lamp was adjusted to 60w / cm2, and the irradiation time was adjusted to 20 seconds.
[0065] Example 6
[0066] On the basis of Comparative Example 2, water phase additives and oil phase additives were added.
[0067] Table 1 Examples of oil phase and water phase additives types and addition amounts
[0068] Types of water phase additives Concentration of water phase additives / ppm Oil phase additives Oil phase additive concentration / ppm Example 1 PEGDE Mn=500 1000 TMTG 100 Example 2 PEGDE Mn=500 3000 TMTG 200 Example 3 PEGDE Mn=500 5000 TMTG 300 Example 4 PEGDE Mn=500 10000 TMTG 400 Example 5 TMP15EOTA 20000 TMPMP 500 Example 6 MBA 30000 TMTG 1000 Comparative Example 3 PEGDE Mn=500 1000 - - Comparative Example 4 - - TMTG 400
[0069] The performance of the membrane was tested and the results are shown in Table 2.
[0070] Table 2 Diaphragm performance test data
[0071]
[0072] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A polyamide composite membrane, wherein a polyamide separation layer is provided on a porous support layer of the polyamide composite membrane, wherein the separation layer has the following characteristics: a. Using attenuated total reflection Fourier transform infrared spectrometer (ATR-FTIR), 2561cm -1 The peak height is 1661cm -1 The peak height ratio is 0.03-0.15%, b. The surface sulfur atom content measured by X-ray photoelectron spectroscopy (XPS) analysis was 0.5-2.5 mol%.
2. A method for preparing a polyamide composite film, the preparation method comprising the following steps: (1) a polyfunctional amine aqueous solution containing a polyfunctional epoxy compound and / or a polyfunctional double bond compound and an oil phase solution containing a polyfunctional acyl chloride and a polyfunctional thiol are contacted and reacted on a porous support layer to form a polyamide separation layer; (2) After the interfacial polymerization reaction is completed, heating and / or ultraviolet irradiation is performed to allow the reaction to proceed fully to obtain a polyamide composite membrane.
3. The preparation method according to claim 2, characterized in that: In step (1), the functionality of the polyfunctional amine is 2-4, and the polyfunctional amine is selected from one or more of aromatic polyamines and aliphatic polyamines; Preferably, the aromatic polyamine is selected from one or more of m-phenylenediamine, p-phenylenediamine, and 1,3,5-triaminobenzene, and the aliphatic polyamine is selected from one or more of ethylenediamine, piperazine, diethylenetriamine, and triethylenetetramine; the multifunctional amine is preferably m-phenylenediamine; Preferably, the concentration of the multifunctional amine in the aqueous solution is 1-8 wt %, preferably 1.5-3.5 wt %.
4. The preparation method according to claim 2 or 3, characterized in that: In step (1), the multifunctional epoxy compound and / or multifunctional double bond compound is selected from any one or a combination of at least two of polyethylene glycol diglycidyl ether, 15-ethoxylated trimethylolpropane triacrylate, and bisacrylamide; Preferably, the concentration of the multifunctional epoxy compound and / or the multifunctional double bond compound in the aqueous phase solution is 0.1-3 wt %, preferably 1-2.5 wt %.
5. The preparation method according to any one of claims 2 to 4, characterized in that: In step (1), the multifunctional acyl chloride is selected from difunctional acyl chloride and / or trifunctional acyl chloride, the difunctional acyl chloride is selected from any one of terephthaloyl chloride, isophthaloyl chloride, and naphthalene dicarboxylic acid chloride or a combination of at least two thereof, the trifunctional acyl chloride is selected from any one of trimesoyl chloride, 1,3,5-cyclohexanetricarboxylic acid chloride, and 1,2,4-cyclobutanetricarboxylic acid chloride or a combination of at least two thereof, and the multifunctional acyl chloride is preferably trimesoyl chloride; Preferably, the concentration of the multifunctional acid chloride in the oil phase solution is 0.08-0.6 wt %, preferably 0.1-0.4 wt %.
6. The preparation method according to any one of claims 2 to 5, characterized in that: In step (1), the multifunctional thiol is selected from 1,2-ethanedithiol, 1,3-propanedithiol, 1,2-propanedithiol, 2,3-butanedithiol, 1,2-butanedithiol, 1,4-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,8-octanedithiol, 1,9-nonanedithiol, 1,10-decanedithiol, 1,2-benzenedithiol, 1,3-benzenedithiol, 1,4-benzenedithiol, tetrakis(ethylene glycol)dithiol, hexa(ethylene glycol)dithiol, and poly(ethylene glycol)dithiol with a number average molecular weight of 1000-8000, trimethylolpropane tris(thioglycolate), trimethylolpropane tris(3-mercaptopropionic acid), and pentaerythritol tetrakis(3-mercaptopropionic acid); Preferably, the concentration of the multifunctional thiol in the oil phase solution is 0.01-0.1 wt %.
7. The preparation method according to any one of claims 2 to 6, characterized in that: The reaction temperature of step (1) is 20-30°C, and the reaction time is 0.5-5 min, preferably 1-2 min.
8. The preparation method according to claim 2, characterized in that: In step (2), the heating is carried out in an oven. Preferably, the oven temperature is 40-90° C. and the residence time is 0.5-2 minutes.
9. The preparation method according to claim 2, characterized in that: In step (2), the ultraviolet irradiation adopts a 254nm short-wavelength ultraviolet lamp, the irradiation power is preferably 60-160w / cm, and the irradiation time is 1-20 seconds.
10. Use of the polyamide composite membrane according to claim 1 or the polyamide composite membrane prepared by the preparation method according to any one of claims 2 to 9 in seawater desalination.
Citation Information
Patent Citations
Anti-pollution and oxidation-resistant reverse osmosis membrane and preparation method thereof
CN115672033A
Anti-oxidation reverse osmosis membrane and preparation method thereof
CN115945072A
Interfacially synthesized reverse osmosis membrane
US4277344A
Cited By
Preparation method of seawater desalination reverse osmosis membrane and seawater desalination reverse osmosis membrane prepared by same
CN121222269A